Penegakan Hukum Lingkungan di Indonesia: Tantangan dan Solusi - Ramadhan, Taufik Ismail (Jurnal Penelitian Multidisiplin Ilmu, 2024)
Environmental law is an important instrument in preserving natural resources and ecosystems. However, the implementation of environmental law in Indonesia faces various challenges, ranging from weak supervision to minimal public awareness. This article aims to analyze the obstacles in enforcing environmental law in Indonesia and provide recommendations for sustainable solutions. This study uses a qualitative method with a descriptive approach. The results show that policy reform, institutional strengthening, and public education are the main keys to increasing the effectiveness of environmental law.